Aromatherapy Candles as Double Protection: A Modern Solution to a Classic Problem - Afriani, Linda; Fajarianto, Otto; Eka Rista Harimurti; Nadiputri, Anggi Nurmutiarani; Putri, Valentina Kusmala (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The problem of mosquito nuisance has long been a challenge for many communities throughout the world. Mosquito bites not only cause discomfort, but also play a role in spreading various dangerous diseases such as malaria, dengue, zika and chikungunya. The innovation of anti-mosquito candles offers an effective solution to overcome mosquito problems in society which often disturb comfort and health. This research examines the effectiveness of anti-mosquito candles that use natural ingredients in reducing mosquito populations and their impact on the environment and human health. The results of this research show that this candle has not only succeeded in reducing the number of mosquitoes significantly but is also safe to use, environmentally friendly, and easy to apply. It is hoped that this innovation can be a better alternative to conventional mosquito repellent methods, while improving people's quality of life by providing efficient and comfortable protection from the threat of mosquitoes. So the innovation of the anti-mosquito aromatherapy candle product not only offers a practical and effective solution, but can also contribute to efforts to protect the environment and public health.